Is continuous assessment inclusive? An analysis of factors influencing student grades - David Playfoot (Assessment and Evaluation in Higher Education, 2022)
This paper reports a series of studies that assessed the performance of students on continuous assessment components from two courses in an undergraduate psychology programme. Data were collected from two consecutive cohorts of students (total N = 576) and the grades of students were compared based on additional learning needs (ALN; ALN versus No ALN), whether or not the students had requested an extension to a deadline, and whether or not students had missed any of the tests that made up the continuous assessment component. Results showed no significant differences in attainment between students with and without ALN, supporting the argument that continuous assessment does not differentially impact students who already require additional support. Students who were granted deadline extensions achieved significantly lower scores, but only on the course with content that built week on week. Students who missed one or more tests achieved significantly lower scores even if the grade was calculated ignoring the questions that a student had not attempted. The implications of these findings for assessment practice in higher education are discussed.